Nature’s Role Toward Mental And Physical Healing Reflected On The Secret Garden By Frances Hudgson Burnett: An Ecocritical Reading - Ignadhitya Herdiana (English Department, Faculty of Humanities, Andalas University, 2018)
This research aims to show the ability of nature to heal mental and physical of children that shown on The Secret Garden written by Frances Hudgson Burnett. The relation of nature and human in this novel are captured on the characters experience the transformation from illness to wellness when interact to the nature in the garden. We might should realize that the main function of literature is not only to entertain but also to teach us how important nature to human. In this case the writer uses qualitative methods and applies eco-criticism to explain how close the relation between nature and human. It means that human and nonhuman have benefited each other and it reflects on how nature or space can be the media of mental and physical healing, and healing power of nature is portrayed in this novel. The writer focuses on: 1) the relation between nature and human, 2) Nature as a media of mental and physical healing to the children depict on the novel interact with space and experience the goodness of nature.